The Green Human Resource Management and Its Implementation in Indonesia - Erwinsyah (Jurnal Bina Ketenagakerjaan, 2021)
The knowledge of green human resource management (Green HRM) is still in an early stage and related to the protection of the environment and maintaining the ecological balance. It contributes to the effort in the implementation of sustainable development, adopted by the national development plan. The purpose of this study is to review the role of human ecology in sustainable development, and the objective of this study is to investigate the implementation of green human resources to sustainable development in Indonesia. The study examines qualitative research using the scientometrics method focused on the analysis of publications from relevant literature and information. The study shows that green human resources are very crucial to achieve sustainable development, promotes effective and efficient production, and minimalizes waste and energy to reduced cost and increased productivity. There are several environmental-based policies implemented in various sectors in Indonesia, but most likely separate from Green HRM practices